تحليل العلاقة السببية والتكامل المشترك بين أداء مؤشر السوق الرئيسي (tasi) وأداء مؤشر السوق الموازي (nomuc) بالسوق المالي السعودي - عباده عبدالرؤوف (جامعة الوادي University of Eloued, 2024)
This study aimed to study the relationship between the performance of the main market index (Tasi) and the performance of the parallel market index (Nomuc) in the Saudi financial market during the period from April 2017 to June 2021, by estimating the vector autoregressive model (VAR) and conducting the cointegration test and the causality test and analysis The response and reaction function and the analysis of the components of variance, and the study concluded that there is no co-integration relationship between the two indicators in the long term, and that there is a oneway causal relationship from the parallel market index (NOMUC) to the main market index (TASI) .
Analysis of the Causal Relationship and Co-integration between the Performance of the Main Market Index (Tasi) and the Performance of the Parallel Market Index (Nomuc) in the Saudi Financial Market
Keywords: مؤشر السوق الرئيسي; مؤشر السوق الموازي; سوق مالي; تكامل مشترك; نموذج شعاع الانحدار الذاتي; Main Market Index; Parallel Market Index; Financial Market; Cointegration; Vector Autoregressive Mode